Spiral CT of the the chest and abdomen - Jeffrey, R. Brooke; Fishman, Elliot K.; Medical Interactive (Firm) (Philadelphia : Lippincott-Raven, 1996)
(Producer) Presents 150 new cases including spiral CT angiography, three-dimensional vascular reconstructions, oncologic applications of spiral CT, and musculoskeletal applications of spiral CT. In addition, there are seven cases with dynamic three-dimensional cine loops. Includes 540 high-quality images.
CD is available at Koleksi Media, Perpustakaan HUKM
System requirements for optical disc: IBM PC or compatible 486 computer; 4 MB RAM; Windows 3.1 or Windows 95; 256 col. VGA card; CD-ROM drive.
System requirements for magnetic disk: PowerPCMac
Keywords: Tomography, X-Ray Computed -- methods -- CD-ROM; Radiography, Thoracic -- CD-ROM; Abdomen -- radiography -- CD-ROM